The Correlation Between Adversity Quotient and Critical Thinking Ability of Chemistry Education Students - Fauziatul Khusna; Wiwik Kartika Sari; Ella Izzatin Nada (Chemistry Education Department, 2023)
In the globalization era, the ability to think critically is a crucial skill for students to navigate through tough competition. One internal factor influencing a person's critical thinking ability is Adversity Quotient (AQ). It provides an overview of how well students can respond and tackle obstacles while honing their essential thinking skills. This study explored the correlation between AQ and students' critical thinking abilities, specifically when working on chemistry problems related to salt hydrolysis. The research involved 30 students majoring in Chemistry Education, selected using a proportional stratified random sampling technique. A questionnaire was administered to measure AQ, while students' critical thinking skills were assessed through a description test. Subsequently, the data were analyzed using the Pearson correlation test, which yielded a correlation coefficient of 0.299, indicating that the correlation between AQ and students' critical thinking skills was not significant (p0.05). Further analysis is required to delve deeper into the correlation between AQ and critical thinking and identify other factors influencing necessary thinking skills.